Epitope Presentation of Dengue Viral Envelope Glycoprotein Domain III on Hepatitis B Core Protein Virus-Like Particles Produced in Nicotiana benthamiana - Pang, Ee Leen; Peyret, Hadrien; Ramirez, Alex; Loh, Hwei-San; Lai, Kok-Song; Fang, Chee-Mun; Rosenberg, William M.; Lomonossoff, George P. (Frontiers in Plant Science, 2019)
Dengue fever is currently ranked as the top emerging tropical disease, driven by increased global travel, urbanization and poor hygiene conditions as well as global warming effects which facilitate the spread of Aedes mosquitoes beyond their current distribution. Today, more than 100 countries are affected most of which are tropical Asian and Latin American nations with limited access to medical care. Hence, the development of a dengue vaccine that is dually cost-effective and able to confer a comprehensive protection is ultimately needed. In this study, a consensus sequence of the antigenic dengue viral glycoprotein domain III (cEDIII) was used aiming to provide comprehensive coverage against all four circulating dengue viral serotypes and potential clade replacement event. Utilising hepatitis B tandem core technology, the cEDIII sequence was inserted into the immunodominant c/e1 loop region so that it could be displayed on the spike structures of assembled particles. The tandem core particles displaying cEDIII epitopes (tHBcAg-cEDIII) were successfully produced in Nicotiana benthamiana via Agrobacterium-mediated transient expression strategy to give a protein of ~54 kDa, detected in both soluble and insoluble fractions of plant extracts. The assembled tHBcAg-cEDIII virus-like particles (VLPs) were also visualised from transmission electron microscopy. These VLPs had diameters that range from 32 – 35 nm, presenting an apparent size increment as compared to tHBcAg control particles without cEDIII display (namely tEL). Mice immunized with tHBcAg-cEDIII VLPs showed a positive seroconversion to cEDIII antigen, thereby signifying that the assembled tHBcAg-cEDIII VLPs has successfully displayed cEDIII antigen to the immune system. If it is proven to be successful, tHBcAg-cEDIII has the potential to be developed as a cost-effective vaccine candidate that confers a simultaneous protection against all four infecting dengue viral serotypes.